Company area within effectiveness of accounting information system - Adisanjaya, Komang; Ramantha, I Wayan (International research journal of management, IT and social sciences, 2018)
This study was about to test and gather the empirical proof about the impact of support from top management, personal ability, AIS formalization development, training, user involvement, and the use of technology to the effectiveness of accounting information system in the mini market of Singaraja city. This study used primary data as the source of data in which the data was quantitative data which was collected by using questionnaire by the staff of the mini market. The data were analyzed by using multiple regression approach. The result showed that the support of top management, personal ability, training, user involvement and the use of technology had positive significant on the effectiveness of accounting information system, then the AIS formalization development had no impact on the effectiveness of accounting information system.